Image Encryption Based on High-Dimensional Manifold Computing and Block Dividing Algorithm - Jia, Meng (International Journal of Optics, 2020)
The image encryption schemes developing more sensitive and more chaotic maps are used as a key sequence generator, such as cascade chaotic maps and high-dimension maps. High-dimension chaotic maps can generate sequences with little correlation after hundred times of iteration. In fact, the sequence is just a flow of the manifold of the chaotic system. A fast way to select sensitive flows of the dynamic systems is introduced in the paper. Combining with the divided blocks diffusion algorithm, the novel scheme yields the cipher image more randomly. Experimental results show that the sensitive flows of the high-dimension system can generate a series with better ergodicity and less correlation compared with the common flows of the same system. The encryption efficiency is enhanced by choosing the sensitive flows of the high-dimension system. The analysis proved that the novel image encryption scheme can resist all common kinds of attacks.